Development of Automatic Identification System (AIS) for Vessels Traffic Monitoring in the Strait of Singapore and Batam Waterways - Saputra, Hendra; Wiratno S, Sapto; Fathonah M, Mufti; Istardi, Didi; Budi K.A, Ardian; Mufida, Mir’atul Khusna; Koto, J (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
AIS (Automatic Identification System) is an automatic tracking system used by ships and vessel traffic service (VTS) for identifying ship information by electronically exchanging data with other vessels, coastal station, and satelite. AIS can be used to monitor vessels traffic on a strait channel by detecting a large number of vessels and collecting the ships information related to ship static, dynamic and voyage information such as MMSI number, navigation status, rate of turn (ROT), ship speed, ship position, course over ground (COG), ship heading (HDG), time stamp, RAIM flag and radio status at once. On this paper we try to develop an AIS system for vessel traffic monitoring purpose in the Strait of Malacca especially in the Strait of Singapore and Batam Waterways as one of the world's most congested straits used for international shipping. The method of AIS system development is divided onto 2 stage. Firstly, AIS raw data sent by ships are recorded and decoded as ships information into an application at once. Secondly, the output of AIS decode is used into web based interactive visualization application to visualize the vessels traffic. The development of AIS system has been tested by running the AIS record, decode and web visualisation and shown that the system could be applied to vessel traffic monitoring.